DEVELOPMENT AND JUSTIFICATION OF THE ESTIMATION ALGORITHM OF THE BONE SYSTEM METABOLISM IN CHILDREN WITH TYPE 1 DIABETES MELLITUS - L. G. Ivchenko; I. M. Bykov; A. A. Basov; F. N. Gilmiyarova; D. A. Domenyuk; G. M.-A. Budaychiev; S. O. Ivanyuta (Кубанский научный медицинский вестник, 2018)
Aim. This study was conducted to develop the optimal methodological approaches to early diagnosis and comprehensive treatment of type 1 diabetes mellitus in children by creating an estimation algorithm of the bone system metabolism based on the results of the studies of calcium phosphorus metabolism, calcium-regulating hormones and bone mineral density.Materials and methods. There was carried out a general clinical, laboratory, X-ray examination of 114 children with type 1 diabetes mellitus aged 7 to 12 years with an endocrinopathy experience from eight months to ten years. The obtained data were compared with the results of the examination of 35 “healthy” and “practically healthy” children of this age group. The densitometric measurement of the bone tissue mineral density in the lumbar spine was performed by the densitometer "Lunar iDXA" with the automatic calculation of the Z-test. Orthopantomography of the jaw bones was carried out by a digital orthopantomograph "ORTHOPHOS XG 3 DS" with the subsequent calculation of the Fuchs index and the X-ray index. Laboratory diagnosis of serum indicators included calcium study (total, ionized), inorganic phosphorus, alkaline phosphatase, calcitonin, osteocalcin, parathormone, 25- Hydroxyvitamin D. Indices of the bone resorption were evaluated by the level of a product of degradation of helical protein collagen type I C-terminal telopeptides (CTx, Beta-Cross laps) in blood serum.Results. At the early stages of development of type 1 diabetes mellitus the speed of bone tissue remodeling increases with increased bone formation. At the late stages of development of endocrine pathology the processes of bone remodeling are slowed down with the predominance of bone resorption processes over bone formation processes as well as a significant decrease in bone mineral density (Z-score <-1SD) with the predominance of criteria "within the expected age norms" and "low mineral density in relation to the average age norm" in the bone tissue structure. A statistically significant decrease in bone mineral density in children with a history of type 1 diabetes mellitus for more than five years is indicative of absolute insulin deficiency of pancreatic β cells as well as an early debut of endocrinopathy during the growth and development of bone tissue, triggering the formation of osteopenic syndrome.Conclusion. The introduction of the algorithm for evaluating bone tissue metabolism based on modern high-tech laboratory radiology methods for diagnosing the state of musculoskeletal system in practical public health will make it possible to identify the pathological changes at early stages, when the implementation of integrated therapeutic and prophylactic measures will have the greatest impact and improve the quality of life of children suffering from type 1 diabetes mellitus.